1996
DOI: 10.1021/bi9516034
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Kinetics of the Reduction of Coenzyme Q Analogs by Complex I (NADH:Ubiquinone Oxidoreductase) in Bovine Heart Mitochondria and Submitochondrial Particles

Abstract: The reduction kinetics of coenzyme Q (CoQ, ubiquinone) by NADH:ubiquinone oxidoreductase (complex I, EC 1.6.99.3) was investigated in bovine heart mitochondrial membranes using water-soluble homologs and analogs of the endogenous ubiquinone acceptor CoQ10 [the lower homologs from CoQ0 to CoQ3, the 6-pentyl (PB) and 6-decyl (DB) analogs, and duroquinone]. By far the best substrates in bovine heart submitochondrial particles are CoQ1 and PB. The kinetics of NADH-CoQ reductase was investigated in detail using CoQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
157
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 154 publications
(167 citation statements)
references
References 74 publications
9
157
1
Order By: Relevance
“…Thus, the DBQ system is apparently more reliable to investigate complex II activity. Notably, it is accepted that DBQ resembles the natural ubichinone chemistry in mitochondria (30). Surprisingly, we found no evidence for an inhibition of complex II at concentrations of up to 20 mM MMA neither in the DBQ (0.5-20 mM: 107-111% of control) nor PMS systems (109 -115% of control; Table I).…”
Section: Fig 2 Involvement Of Ionotropic Glutamate Receptors Oxidacontrasting
confidence: 51%
“…Thus, the DBQ system is apparently more reliable to investigate complex II activity. Notably, it is accepted that DBQ resembles the natural ubichinone chemistry in mitochondria (30). Surprisingly, we found no evidence for an inhibition of complex II at concentrations of up to 20 mM MMA neither in the DBQ (0.5-20 mM: 107-111% of control) nor PMS systems (109 -115% of control; Table I).…”
Section: Fig 2 Involvement Of Ionotropic Glutamate Receptors Oxidacontrasting
confidence: 51%
“…Using HAR, the upper limit of NADH/Q activity of complex I was calculated to be 14 Ϯ 1 units/mg complex I. These values of complex I NADH/Q activity fall in the middle of estimates of complex I NADH oxidase activity in SMPs, which range from ϳ4 to 30 units/mg complex I measured using a variety of Q analogues (45,(52)(53)(54). Our value of 12-14 units/mg agrees closely with the NADH/DQ activity of ϳ14 units/mg complex I measured in bovine heart SMPs by Fato et al (originally reported as k cat ϭ 225 s Ϫ1 (52)).…”
Section: Subunitmentioning
confidence: 99%
“…The protein concentration of the flavin domain and the Fe-S domain was standardized by UV spectroscopy using the calculated extinction coefficients at 280 nm based on the content of aromatic amino acid residues of the apoproteins. The concentrations of NADH (⑀ 340 ϭ 6.22 mM (30) and FAD (⑀ 450 ϭ 11.3 mM Ϫ1 cm Ϫ1 ) (31) were calculated based on their absorption coefficients.…”
Section: In Vitro Reconstitution Of the Fe-s Cluster-insertion Of Thementioning
confidence: 99%